2015
DOI: 10.1016/j.ejmg.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Identical by descent L1CAM mutation in two apparently unrelated families with intellectual disability without L1 syndrome

Abstract: Mutations in the L1 Cell Adhesion Molecule (L1CAM) gene (MIM#308840) cause a variety of X-linked recessive neurological disorders collectively called L1 syndrome. Using massively parallel sequencing (MPS) of the X-chromosome exome, we identified a novel missense variant in L1CAM in two Caucasian families with mild-moderate intellectual disability without obvious L1 syndrome features. These families were not known to be related. SNP data extracted from MPS identified a 5.6 cM tract of identity by descent (IBD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…1) as described by Hu et al (11). Subsequent whole-genome sequencing and alignment was performed on IV:6 and VI:1 as previously described (126). Using genomic DNA from the proband and parents, the exonic regions and flanking splice junctions of the genome were captured using the Clinical Research Exome kit (Agilent Technologies, Santa Clara, CA).…”
Section: Dna Sequencing and Alignmentmentioning
confidence: 99%
“…1) as described by Hu et al (11). Subsequent whole-genome sequencing and alignment was performed on IV:6 and VI:1 as previously described (126). Using genomic DNA from the proband and parents, the exonic regions and flanking splice junctions of the genome were captured using the Clinical Research Exome kit (Agilent Technologies, Santa Clara, CA).…”
Section: Dna Sequencing and Alignmentmentioning
confidence: 99%
“…In practice, long tracts of IBD (>3 cM) can be accurately detected using genetic data between individuals with a common ancestor from the past 4–50 generations ( Browning and Browning, 2012 ). Detection of IBD haplotypes can allow for the identification of distantly related patients with a genetic disorder driven by a locus inherited from a founding ancestor who brought the disease mutation into a population ( Houwen et al, 1994 ; Kenny et al, 2009 ; Henden et al, 2016 ; Meta-Analysis of Glucose and Insulin-related traits Consortium (MAGIC) et al, 2010 ; Traherne et al, 2016 ; Shaw et al, 2015 ; Ko et al, 2014 ; Lalli et al, 2014 ). This is the principle underlying population-scale disease mapping approaches that combine IBD sharing and statistical association to discover novel disease loci, so called IBD-mapping.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that (rs28933690) (C294R) pathogenic, which is matched with the clinical result that we retrieved from dbSNPs/NCBI database .also we Retrieved (rs145996031) (Y370D) as untested we found to be damaging. Interestingly we found that, (rs145996031) (Y370D) novel SNP may also cause L1 syndrome (53).…”
Section: Discussionmentioning
confidence: 72%